MENINGKATKAN NILAI PENDIDIKAN MELALUI TIGA KONSEP DASAR FALSAFAH WETU TELU DI DESA SAPIT - Novayani, Irma (eJurnal Al Musthafa, 2024)
Education is a source of character formation in humans. Education does not only teach about science but also instills life values ​​which are indicators of the usefulness of a science. Wetu Telu as a philosophy of life in the people of Sapit to this day still adheres to the principles of the Wetu Telu philosophy, namely by obeying parents, obeying teachers, and obeying leaders. These three things are the basic concepts in the Wetu Telu philosophy which must be the principles for maintaining harmony both with oneself and among others. In education, these three things become a unity that supports each other as a forum for developing character and knowledge